1998
DOI: 10.1177/1059601198231003
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Workplace Affirmative Action Plans

Abstract: Affirmative action in the workplace continues to be a controversial issue, particularly for persons soon to enter the workforce. This study examines psychological constructs and demographic variables as precursors to perceptions of the self-interest implications of affirmative action programs. The constructs of symbolic prejudice and self-esteem were found to predict perceptions toward affirmative action in the workplace. Weak effects were found for race and gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…These data confirm, in line with several studies (e.g., Heilman, Simon, & Repper, 1987;Little et al, 1998), that affirmative action can contribute to reinforce the discrimination of targets. For example, Heilman, Block, and Stathatos (1997) showed that lower wages were proposed to a female applicant who was presented as benefiting from an affirmative action in hiring process than to a control female target.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These data confirm, in line with several studies (e.g., Heilman, Simon, & Repper, 1987;Little et al, 1998), that affirmative action can contribute to reinforce the discrimination of targets. For example, Heilman, Block, and Stathatos (1997) showed that lower wages were proposed to a female applicant who was presented as benefiting from an affirmative action in hiring process than to a control female target.…”
Section: Discussionsupporting
confidence: 81%
“…One way to implement diversity is to treat preferentially members of some target groups. Unfortunately, deleterious effects of preferential treatment on target's perceived competence have been repeatedly shown both when the association between the target and an affirmative action program was made explicit and when this link was only implicit (e.g., Heilman, McCullough, & Gilbert, 1996;Heilman & Welle, 2006;Little, Murry, & Wimbush, 1998;Moore, 1999;Nacoste, 1990). As a case in point, Heilman and colleagues (1992) presented a bogus female hire as being associated or not with an affirmative action program.…”
mentioning
confidence: 99%
“…Generally, the more discrimination a group experiences, the more positively they view affirmative action plans (Kravitz & Platania, 1993). Therefore, women traditionally have evaluated affirmative action more positively than men (Bobocel, Son Hing, Davey, Stanley, & Zanna, 1998;Kravitz & Platania, 1993;Little, Murry, & Wimbush, 1998;Ozawa, Crosby, & Crosby, 1996), and minorities (African Americans and Latinos) hold more favorable views toward affirmative action than do Caucasians (Bobocel et al, 1998;Kravitz & Platania, 1993;Little et al, 1998). It can be argued that Caucasian males tend to hold the most negative attitudes toward affirmative action because they are the least likely to be beneficiaries of affirmative action.…”
Section: Affirmative Action Programsmentioning
confidence: 99%
“…Generally, the more discrimination a group experiences, the more positively the group views affirmative‐action plans (Kravitz & Platania, ). Therefore, women have traditionally evaluated affirmative action more positively than have men (Bobo, ; Kravitz & Platania, ; Little, Murry, & Wimbush, ; Ozawa, Crosby, & Crosby, ), and minorities have more favorable views toward affirmative action than do Whites (Awad, Cokley, & Ravitch, ; Bobo, ; Kravitz & Platania, ; Little et al., ). However, when the focus is on ethnic minority affirmative‐action beneficiaries (e.g., Blacks or Hispanics), White women's attitudes toward the policy tend to be more similar to those of men (Awad et al., ).…”
mentioning
confidence: 99%
“…Research has indicated that there is a relationship between affirmative‐action attitudes and racial attitudes (Awad et al., ; Durrheim et al., ; Federico & Sidanius, ; McConahay, ; Oh, Choi, Neville, Anderson, & Landrum‐Brown, ). People high in modern racism tend to report negative attitudes toward affirmative action (Awad et al., ; Bobo, ; Little et al., ; McConahay, ). In addition, attitudes toward affirmative action are also impacted by political ideology.…”
mentioning
confidence: 99%